Efektifitas Penanganan Kecelakaan Lalu Lintas Melalui Restorative Justice di Polres Baubau - Mustafa, La Ode Ali; Samaluddin, Samaluddin; Done, Hardi (IAIN Langsa, 2023)
This study aims to determine the role of traffic police in handling traffic accident cases through RJ at Baubau Police Station. This research was conducted at Satlantas Polres Baubau. The method used in this research is empirical legal research with data collection through document study and interviews. Sampling was done non randomly with a purposive sampling technique. The data was analyzed using qualitative analysis. The results showed that the settlement of accident cases through restorative justice in 2021–2022 was 306 cases. The obstacles to settlement carried out through Alternative Dispute Resolution (ADR) are carried out by bringing together the victim and the perpetrator. After being brought together, mediation is carried out, which ends with a peace agreement. With a peace agreement. And through Restorative Justice, the restorative justice approach is an option given by the police to the parties involved in a criminal offense. police to the parties involved in a criminal offense. Traffic accident cases can be resolved in a restorative justice process, which is a family settlement to produce a win-win solution for both parties without having to go through the legal process.